KREATIFITAS PRODUSER DAN JURU KAMERA DALAM FILMDOKUMENTER"TUNGGANGAN SANG PANGERAN" - Muhammad Akbar Fahlevi (2024)
The documentary entitled "Tunggangan sang pangeran" is a film that documents the Kuda Kosong culture which is the culture of the District. Cianjur. This documentary is an observatory type film with a narrative style. This film discusses the conflict between cultural actors and the Cianjur MUI (Majelis Ulama Indonesia), until the Cianjur MUI issued a "Haram" fatwa because of the mystical rituals involved in it regarding the Kuda Kosong. This film also discusses the facts behind the conflict with Kuda Kosong. The producer's creativity in this film is very important from the beginning to the end of the film and the cameraman in this film is tasked with taking pictures that will later be assembled into a film. This film was made to provide information regarding the Kuda Kosong culture, which is a unique culture from Cianjur, West Java and is an example if something similar happens in other areas